Is the Allocation of Resources within the Household Efficient? New Evidence from a Randomized Experiment. - Bobonis, Gustavo J. (Journal of Political Economy, 2009)
I study whether households make Pareto-efficient intrahousehold resource allocation decisions. Combining randomized variation in women's income generated by the evaluation of the Mexican PROGRESA program with variation attributable to localized rainfall shocks as distribution factors in the collective model, I find evidence favoring Pareto optimality. More specifically, female-specific income changes have positive effects on children's goods expenditures, whereas changes due to rainfall shocks have a smaller influence on household public goods expenditures. The evidence is consistent with female partners having greater sensitivity to own-income changes and norms that oblige women to devote their earnings to meet collective consumption needs. Reprinted by permission of the publisher.